Obesity as a Risk Factor for Cardiovascular Diseases in Women: Pathogenesis, Clinical Features, and Modern Prevention Methods - Bekimbetova Mehriban (Genius Journals, 2025)
Obesity is one of the most pressing public health issues in the modern world. According to the World Health Organization (WHO), the number of overweight patients has significantly increased in recent decades, leading to a rise in cardiovascular disease (CVD) incidence [1]. Women with obesity have a significantly higher risk of developing hypertension and metabolic syndrome, as confirmed by numerous epidemiological studies [2]. Despite the large number of studies on obesity, the management strategies for women with obesity and a high risk of cardiovascular diseases remain insufficiently studied. Modern prevention and correction methods should include not only diet therapy and physical activity but also pharmacological strategies aimed at improving metabolic status and reducing inflammatory processes [3]. Thus, studying obesity as a risk factor for cardiovascular diseases in women and searching for modern approaches to prevention and treatment are crucial tasks of contemporary medicine.
Keywords: obesity; cardiovascular diseases; arterial hypertension